Proceedings EUMCCI-UTM Seminar on Ocean Energy : AQUA POWERING THE FUTURE, MENARA RAZAK, UTM KUALA LUMPUR - EUMCCI-UTM Seminar on Ocean Energy : Aqua Powering the Future (2017 : Kuala Lumpur); A. Bakar Jaafar, editor; Benetello, Roberto, editor; Mohammad Shafiq Rahmat, editor; EU-Malaysia Chamber of Commerce and Industry, organizer (Kuala Lumpur : UTM Ocean Thermal Energy Centre, Universiti Teknologi Malaysia, 2017)
Includes index